An overview of traditional smoking cessation interventions and E-cigarettes - Alshehri, Fahad S. (Frontiers in Pharmacology, 2024)
Many people still struggle with quitting smoking despite available treatment options, making it one of the most significant public health challenges that our society faces. The use of electronic cigarettes (E-cigarettes) has become increasingly popular among people who are seeking to quit smoking. The objective of this review paper is to present a comprehensive analysis of the mechanisms, several types, and impact of E-cigarettes, along with supporting evidence indicating their efficacy in aiding smokers to quit tobacco usage.Additionally, the review discusses recent developments in the treatment of smoking cessation, which include conventional smoking cessation methods. Also, the review discusses the challenges, potential risks, ethical considerations, and controversies surrounding the use of E-cigarettes. The present review presents a comprehensive examination of the existing methods and approaches employed in smoking cessation, including the emerging utilization of E-cigarettes as an effective option in smoking cessation. It explores their efficacy as a valuable instrument in promoting smoking cessation.